Energy consumption evaluation in trust and reputation models for wireless sensor networks - Alkalbani, Abdullah Said; Md Tap, Abu Osman; Mantoro, Teddy (2013)
In this paper, popular trust and reputation models for Wireless Sensor Networks (WSNs) is studied. Accuracy, scalability and power consumption are the main challenges during the routing of data. High power consumption reduces network lifetime. Due to the lack in researches that compare between trust and reputation models especially in terms of energy efficiency this paper presents comparison between several proposed trust and reputation models in terms of average path length, average accuracy and energy consumption rate.